2016
DOI: 10.1124/dmd.115.067413
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Supports CYP2D-Mediated Serotonin Synthesis in the Brain

Abstract: Melatonin is used in the therapy of sleep and mood disorders and as a neuroprotective agent. The aim of our study was to demonstrate that melatonin supported (via its deacetylation to 5-methoxytryptamine) CYP2D-mediated synthesis of serotonin from 5-methoxytryptamine. We measured serotonin tissue content in some brain regions (the cortex, hippocampus, nucleus accumbens, striatum, thalamus, hypothalamus, brain stem, medulla oblongata, and cerebellum) (model A), as well as its extracellular concentration in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Excessive exposure to a screen, especially in the late evening, can have a detrimental effect on sleep. This is probably because of the blue light projected from the screens in which affects the natural production of melatonin, a hormone the body produces to help us sleep [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive exposure to a screen, especially in the late evening, can have a detrimental effect on sleep. This is probably because of the blue light projected from the screens in which affects the natural production of melatonin, a hormone the body produces to help us sleep [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…At the level of the hypothalamus-preoptic area, serotonin stimulates the HPI axis by increasing Crh release, which boosts the downstream GC stress response (125, 134). Studies have revealed that melatonin can interact with serotonin to modulate its function (109, 130, 135). Moreover, melatonin ability to reduce stress in teleosts has been usually associated with simultaneous changes in brain serotonergic activity (109, 130, 133).…”
Section: Stress and Melatonin Interplay In A Rhythmic Environmentmentioning
confidence: 99%
“…[26]. Recently, in 2020 and due to COVID19 pandemic outbreak and associated con nement, increased levels of psychological problems such as anxiety, depression and poor sleeping quality were found among Chinese quarantined participants [19,20,21]. Furthermore, a recent review concluded that quarantine deteriorate peoples' mental health causing negative psychological effects including post-traumatic stress symptoms [27,28].…”
Section: Table 2 Assessment Of Mental Wellbeing According To Lifestymentioning
confidence: 99%
“…This is probably because of the blue light from the screens that affects the natural production of melatonin, a hormone the body makes to help us sleep. [19,20,21] Finally, Mental wellbeing is an important issue in our daily life and may change from day to day. Each person has a different potential to cope with stress and can be affected by several factors.…”
Section: Introductionmentioning
confidence: 99%